Tratamento silvicultural de desbaste de liberação em uma floresta ombrófila densa no estado de Roraima, Amazônia brasileira - Cordeiro, Lorenza Zanetti Silva (2012)
This study presents the results of the analysis of technical efficiency and costs of silvicultural treatments carried out in a lowland Amazon rainforest logged under reduced impact logging guidelines. The silvicultural treatments consisted in the postharvest girdling and herbicide treatment (using the product Tordon in 50% solution) of remnant trees competing with future crop trees (FCTs). In order to analyze the effect of girdling on tree mortality, a binary logistic model was utilized. The model indicated a slower mortality process for secondary tree species. On average 21,6 competing trees per hectare were girdled in order to benefit 12 FCTs per hectare (on average 1,8 competitors for every FCT). Results demonstrate the high efficiency of the silvicultural treatments tested: mortality of competitors attained 69% within six months after girdling and 100% within twelve months after girdling. The total cost of girdling amounted to BRL 77,88 per ha, BRL 3,59 per girdled tree and BRL 5,56 per FCT. Of the total cost, 50% arose from production factors, especially herbicide acquisition, while 47% were labor costs. Only 2% of the total costs were generated from work safety equipment and 1% of other materials. The operative productivity attained 0,76 man days per hectare which included the activities competitor identification, climber cutting, girdling and herbicide application.